Electrochemical Properties of LiCoO2 Electrodes with Latex Binders on High-Voltage Exposure. Issue 4 (1st January 2015) - Yabuuchi, Naoaki; Kinoshita, Yuta; Misaki, Kimio; Matsuyama, Takashi; Komaba, Shinichi
Abstract : Styrene–butadiene rubber (SBR) latex with carboxymethyl cellulose (CMC) is applied as a water-dispersible binder for LiCoO2 particles, and electrochemical behavior on high-voltage exposure in non-aqueous Li cells is compared with that of a conventional PVdF binder. LiCoO2 electrode with SBR/CMC binder (LiCoO2 : AB : SBR : CMC = 80 : 10 : 0.5 : 1.5 in weight ratio) delivers approximately 180 mAh g −1 of initial discharge capacity with high cutoff voltage of 4.5 V. Moreover, excellent capacity retention, without increase in the polarization, is achieved even with 4.5 V cutoff whereas capacity degradation is observed for the PVdF electrode. The mechanism of improvement for the LiCoO2 electrodes with SBR/CMC are examined by peel test, transmission electron microscopy, and X-ray photoelectron spectroscopy, and results are compared with those of the PVdF electrode. The composite electrode with the SBR/CMC binder shows much higher adhesive strength than that with the PVdF binder even though SBR is found to be electrochemically oxidized above 4.2 V. In addition, formation of phosphorus- and fluorine-containing layer on active material, which is presumably derived by electrolyte decomposition, is suggested to be responsible for the excellent capacity retention on high-voltage cycles.